2013
DOI: 10.1007/s13534-013-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a finite-element reciprocity method for epileptic EEG source localization: Accuracy, computational complexity and noise robustness

Abstract: Purpose: The aim of this paper is to evaluate the performance of an EEG source localization method that combines a finite element method (FEM) and the reciprocity theorem. Methods: The reciprocity method is applied to solve the forward problem in a four-layer spherical head model for a large number of test dipoles. To benchmark the proposed method, the results are compared with an analytical solution and two state-of-the-art methods from the literature. Moreover, the dipole localization error resulting from ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The direct method, in contrast, requires thousands of iterations to create a leadfield from a dense array of sources. A number of previous studies have demonstrated the use of reciprocity for FEM solutions [22,2,3,7]. This article draws heavily on the work of Weinstein et al for its basis [22].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The direct method, in contrast, requires thousands of iterations to create a leadfield from a dense array of sources. A number of previous studies have demonstrated the use of reciprocity for FEM solutions [22,2,3,7]. This article draws heavily on the work of Weinstein et al for its basis [22].…”
Section: Introductionmentioning
confidence: 98%
“…In this paper we focus on the forward problem, which has not been given a great deal of attention in neuroimaging. Despite many published studies demonstrating high-quality head models and forward modeling approaches [2,3,4,5,6,7,8], most functional neuroimaging studies still rely on relatively poor quality electromagnetic head models when performing source localization.…”
Section: Introductionmentioning
confidence: 99%
“…In EEG/MEG analyses, the reciprocity principle has been previously used for BEM [27], [28], [32], FDM [29], [28], [32], and FEM [31], [32], [33], [34] methods, but its applications have generally been limited. This is perhaps because, for identical head models, both conventional (dipole-based) and reciprocal (electrode-based) approaches are very similar in the final result for EEG applications, as they both change the forward problem from a source point of view to a sensor point of view [31].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this task is to estimate an average noiseless EEG source localization floor for a deeplylocated tangential cortical dipole cluster, with the response resembling that of the N20/P20 peak. Some previous studies reported very high ideal source reconstruction accuracy, such as twice the size of the discretization element [33]. However, these studies were either restricted to spherical head models [28], [29], [30], [33] and/or to one subject [29], [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation